Application of the ECLECTIC Framework on a Pediatric Case. (30th August 2019) - Moss, N; MacDonald, B
Abstract: Objective: The ECLECTIC Framework (Fujii, 2018) provides seven components that are pertinent for understanding culturally diverse cases. Education and literacy, Culture and acculturation, Language, Economics, Communication, Testing situation, Intelligence conceptualization, and Context of immigration may impact neuropsychological test performance. Presented within this pediatric case study are examples of common difficulties encountered in conducting evaluations with ethnic and linguistic minorities, as well as considerations to increase equity and validity throughout the evaluation process. Case Description: Maria is a 10-year-old, Spanish speaking female who moved from Cuba to the United States in November 2017. Maria relocated with her mother, who was pregnant at the time, and the family lives with Maria's maternal great aunt. Per evaluations completed in Cuba, Maria has a history of intellectual disability, scoliosis, and untreated seizures. Although not documented, Maria's mother reported that Maria has a prior diagnosis of "mild autism" made in Cuba. Maria receives special education services in the United States and previously received services in Cuba. Home language and academic instruction are in Spanish. Diagnostic Impressions and Outcomes: Cognitive abilities are severely impaired and similar to those of a child between the ages of 2 and 4, with social skills showing more delay. Diagnosis of Autism Spectrum Disorder, with accompanying intellectual (Intellectual Disability, Severe) and language impairments is confirmed. A family history of intellectual deficits due to a genetic condition was reported. Consultations with both Neurology and Genetics/Dysmorphology services are highly recommended to understand the etiology of Maria's significant and globally diffused impairments. Discussion: For pediatric cases, the ECLECTIC Framework requires the components to consider the child in the context of their family and the intersectionality between parent and child. References: Fujii, D. E. (2018) Developing a cultural context for conducting a neuropsychological evaluation with a culturally diverse client: The ECLECTIC framework.  The Clinical Neuropsychologist,  32 (8),  1356-1392, DOI: 10.1080/13854046.2018.1435826 .